Synthesis of imogolite mineral in laboratory conditions - Bắc, Bùi Hoàng; SONG, YONGOO (Vietnam Journal of Earth Sciences, 2012)
In this paper, the authors introduce one type of nanomineral, imogolite, which is, currently, in the interest of many scientists. Based on characteristics  of chemical compositions and natural forming conditions, imogolite is synthesized by combining a solution of AlCl3 with Si(OC2H5)4. Different experimental conditions, such as concentrations of initial sources (2, 5, 10, 25 and 50mM), reaction periods (2, 5, 10 and 15 days) and temperature of 96°C, are checked carefully. The synthesized products are analyzed by using XRD, FT-IR and TEM instruments. The results indicated that pure imogolite can be successfully synthesized under experimental conditions of 2mM of AlCl3 - Si(OC2H5)4, reaction period of 2 days and temperature of 96°C.